Improving Chemistry Teacher Competence in Compiling Chemistry Learning Modules Oriented to Strengthening Pancasila Student Profiles Assisted by the GPT Chat Application - Sudarmin, Sudarmin; Dewi, Siti Herlina; Susatya, Eko Budi; Harjono, Harjono; Kasmui, Kasmui; Eralita, Norma; Pujiastuti, Rr. S.E; Damayanti, Yosephine Debbie (Universitas Negeri Semarang, 2024)
The community service activity's background stems from observations, interviews, and data collected during Field Experience Practice and Teacher Professional Education mentoring activities for prospective science and chemistry education teachers. It was identified that candidates need enhancement in developing chemistry teaching modules oriented toward the Pancasila Student Profiles (PSP). The activity aims to address this issue by providing competency training in preparing chemistry teaching modules oriented to Pancasila Student Profiles using the GPT Chat application. The target audience for the activity includes chemistry teachers who are members of MGMP Semarang and Kudus, with approximately 25 participants. The activities include training and mentoring through In-House Training, assistance in creating chemistry teaching modules oriented towards Pancasila Student Profiles, and assessment of the developed teaching modules. Based on the data from the community service activity implementation, the following conclusions can be drawn: (1) training participants have increased their competency in compiling chemistry teaching modules oriented towards strengthening the profile of Pancasila students, (2) chemistry teaching modules oriented towards strengthening the profile of Pancasila students have been produced with good and excellent quality, (3) the response of the target audience from the community service activity indicates a positive impact.